Hidden allies for value chain responsibility? A system theory perspective on aligning sustainable supply chain management and trade compliance - Baier, Carolin; Beckmann, Markus; Heidingsfelder, Jens (International Journal of Physical Distribution & Logistics Management, 2020)
Purpose: The paper investigates how the alignment of two corporate functions, sustainable supply chain management (SSCM) and trade compliance (TC) can help companies to take corporate value chain responsibility (VCR). In particular, the authors investigate how evolutionary system theory can explain the coevolution of two distinct VCR functions (SSCM and TC) and the potential and challenges for their future alignment. Design/methodology/approach: The authors introduce evolutionary system theory as a powerful explanatory perspective to the field of VCR, SSCM and TC. By applying evolutionary system theory to the VCR debate, the authors analyze the potential for aligning both functions. They further analyze the inherent challenges of such an alignment by discussing the concept of organizational path dependencies. Findings: The paper spells out a research agenda and formulates testable propositions for further investigating the interplay of environment and system as well as the structural options for a functional alignment of SSCM and TC. Originality/value: The corporate function of TC has been widely overlooked by supply chain and sustainability scholars. This paper adds the function of TC to the wider discussion on SSCM and corporate VCR. Furthermore, the paper develops a research agenda for a pioneer topic and triggers discussion in academia and corporate practice.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Evolutionary system theory; Organizational path dependency theory; Sustainable supply chain management; Trade compliance; Value chain responsibility; Nachhaltigkeit